ANALISIS MANAJEMEN PELAYANAN AKTA KELAHIRAN DI KELURAHAN MEDOKAN AYU KOTA SURABAYA - Widuri, Ocha Aulia; Wibawani, Sri (Jurnal Progress Administrasi Publik, 2024)
A birth certificate is a document that every citizen in Indonesia must have as legal proof of a person's identity issued by the Population and Civil Registration Service of the City of Surabaya. Following digital developments, the management of birth certificate services has become different from before. Digitalization must also make all public services innovative. The Surabaya City Population and Civil Registry Department created a KNG (Klampid New Generation) innovation as an online population administration service. There are problems with birth certificate services in Medokan Ayu Village related to websites that sometimes have errors, long document verification processes, data input errors by residents, and even incomplete files. This research aims to analyze the effectiveness of birth certificate service management. The research method used is descriptive qualitative with the type of action research. Data collection techniques through interviews, observation, and documentation. The research focus is based on public management principles, namely 1) Accountability, 2) Transparency, 3) Responsive, 4) Professional, 5 Effectiveness, 6) Efficient, 7) Adaptive, 8) Rational. The results of the research show that the accountability of the population administration officers can be held accountable by not abusing citizen data, transparency of the KNG which can be accessed by all residents of the city of Surabaya, fast responsiveness regarding file submissions, the effectiveness of the birth certificate service can provide output results of birth certificate documents with the ease provided, efficiency of time and energy by residents and Adminduk officers, adaptation to face differences in submitting birth certificate files, rationality with a systematic flow, requirements and time period for issuing birth certificates that are clear, professionalism of Adminduk service officers as proven by the "Integrity Pacts" oath. So that the effectiveness of birth certificate service management can provide benefits from the output results provided.   Keywords: Management; Public Service; Administration